Philosophical reflections on tourism - Stanisław Zaborniak; Bogdan Mytskan; Tetiana Mytskan; Natalia Protsyshyn; Iryna Ivanshyn; Patrycja Żegleń (Jan Długosz University in Częstochowa, 2019)
The aim of the article is to reveal the essence of tourism as means of outlook formation of a person. The following research methods were used in the paper: desk research analysis of the literature on the subject, Internet sources. Analysis of the collected material allowed the following conclusions: one of the factors influencing tourism development is the need to verify traditional understanding of tourism. According to the authors, ideological, cultural, humanistic, ethical, cognitive, ets. aspects of tourism should be emphasized. Taking this into account, we consider tourism as a factor influencing general worldview of man. In this regard, tourism gives reasons to perceive it from a philosophical perspective, including epistemological, social, axiological, spiritual and other aspects. When considering the phenomenon of tourism from a philosophical point of view, it should be emphasized that tourism promotes unification, communication and socialization as well as the spread of ethical values in a spirit of mutual understanding and respect.